MICROTEACHING: Analysis of the Readiness of Prospective Mathematics Teacher Students in Teaching Function Material - Akhsanul In'am; Rani Darmayanti; Ahmad Hariyadi; Wita Wahyu Mardiningrum; Dewi Nurmalitasari (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
In today's era of globalization, teacher professionalism is inevitable and cannot be postponed as competition becomes increasingly fierce. We need people who are indeed experts in their field, according to their abilities, so that everyone can play their role optimally. This study aims to describe the ability of students in a mathematics teaching research program to prepare to become professional teachers based on the teaching skill standards needed in the future to become teachers. In microteaching courses. Through micro-teaching, teachers gain knowledge and skills on how to plan and practice learning activities that will be provided to students so that learning becomes meaningful and they can become professional teachers. The type of research is qualitative, with the research subjects being three students conducting research in preparation for a micro-teaching course in semester odd of the 2023/2024 academic year. The tools used are learning planning rubrics, teaching practice observation sheets, practical skills assessment sheets, and practical activity notes—data collection techniques by observation, interviews and documents. Based on the analysis results, it was found insight and concluded that students of the study program Teaching Mathematics in Micro-teaching course have the potential to become professional teachers based on the skills education, specifically educational, personal, professional and social skills